Assessment of wind power potential for turbine installation in coastal areas of Turkey - Ucar, Aynur; Balo, Figen (Pergamon-Elsevier Science Ltd, 2010)
This paper analyses the potential and the feasibility basis for the wind energy resources in some locations of coastal regions of Turkey. The dominant wind directions, the mean values, wind speeds, wind potential and the frequency distributions were determined. The results showed that Balikesir and Canakkale among annual averages show higher value of mean wind speed. The mean annual value of Weibull shape parameter k is between 1.54 and 1.86 while the annual value of scale parameter c is between 2.52 m/s and 8.34 m/s. A technical assessment has been made of electricity generation from four wind turbines having capacity of 600 kW, 1500 kW, 2000 kW and 2500 kW. The yearly energy output and capacity factor for the four different turbines were calculated. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Wind energy; Wind power potential; Wind turbine